FRI0219 CD4+CD25+FOXP3+ REGULATORY T CELLS IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS: THE NEGATIVE ASSOCIATION WITH DISEASE ACTIVITY, ACUTE COURSE, TRANSITIONAL B CELLS AND IGG LEVELS. (June 2019) - Aleksandrova, Elena; Mesnyankina, Anna; Novikov, Alexander; Aleksankin, Andrey; Solovyev, Sergey; Lukina, Galina
Abstract : Background: CD4+ CD25+ Foxp3+ regulatory T (Treg) cells play a key role in maintaining peripheral tolerance and preventing autoimmune disease. Quantitative and/or qualitative deficiencies of Treg have been associated with immune disturbances in systemic lupus erythematosus (SLE). Objectives: The main goal of the study was to determine the relationship of CD4+CD25+FoxP3+Treg cells with clinical and immunological manifestations in SLE patients (pts). Methods: Frequencies and absolute numbers of peripheral blood CD4+CD25+FoxP3+Treg cells were assessed in 21 healthy donors and 20 SLE pts (2012 SLICC classification criteria); (1M/19F); age 32±13 years; disease duration median (25–75 percentile) 5(1-10) years; SLEDAI2K≥10 - 15(10-22) (14 pts), <10 – 7(6-8) (6 pts). All pts were treated with prednisone, hydroxychloroquine, azathioprine, mycophenolate mofetil, clophosphamide. CD4+CD25+FoxP3+ Treg cells and B-cell subsets were analyzed using multicolor flow cytometry. Results: Compared with healthy donors, SLE pts demonstrated significant lower the absolute number of Tregs (0.05; 0.04-0.06 vs 0.03;0.02-0.05x10 9 /L, p<0, 036), with a high percentage of Treg (8.8;7.5-10.5 vs 12.0;8.8-17.0%, p<0.02). The median percentage of Tregs was lower in pts with acute SLE compared to chronic SLE pts (9.0;8.3-9.9 vs 13.5;12.7-18.7%, p<0, 02). SLE pts with high activity had a lower frequencies of Tregs (10.2;8.5-15.0 vs 15.8;12.7-20.4%, r=-0, 51, p<0, 05). Low count of Tregs correlated with elevated level of IgG (r=-0, 52, p<0, 05). Absolute number of Tregscorrelated negatively with percentage and absolute count of transitional (CD19+IgD+CD10+CD38++CD27-) B cells (r=-0, 66 and r=-0, 63, p<0, 05). Conclusion: Decreased amount of T regs in SLE is associated with high disease activity, acute course and expansion of autoreactive B cells. References: [1] Zhang SX, Ma XW, Li YF, Lai NL, Huang ZH, Fan K, Wang CH, Li XF. The Proportion of Regulatory T Cells in Patients with Systemic Lupus Erythematosus: A Meta-Analysis. J Immunol Res. 2018 Sep 3;2018:7103219. doi: 10.1155/2018/7103219. [2] Żabińska M, Krajewska M, Kościelska-Kasprzak K, Jakuszko K, Bartoszek D, Myszka M, Klinger M. CD4(+)CD25(+)CD127(-) and CD4(+)CD25(+)Foxp3(+) Regulatory T Cell Subsets in Mediating Autoimmune Reactivity in Systemic Lupus Erythematosus Patients. Arch Immunol Ther Exp (Warsz). 2016 Oct;64(5):399-407. doi: 10.1007/s00005-016-0399-5. Disclosure of Interests: None declared